Antimicrobial Potential of Transition Metal Hexacyanoferrates - Arora Chugh, Charu; Bharti, Dipti (Asian Journal of Chemistry, 2012)
Six transition metal hexacyanoferrates namely manganese, cobalt, nickel, copper, zinc and cadmium ferrocyanides have been synthesized and characterized on the basis of IR, elemental analysis, magnetic susceptibility measurement and thermal analysis. Antibacterial screening of synthesized metal ferrocynides has been carried out against Escherichia coli 101, Escherichia coli 119, Pseudomonas fluorescence, Micrococcus luteus, Bacillus subtilis and Bacillus cereus. M. luteus causes asthma while B. subtilis and B. cereus cause food poisoning. Rest of the other strains are non pathogenic. Copper ferrocyanide has shown potential activity against E. coli 119, E. coli 101 and B. cereus. Cobalt ferrocyanide has been found to be most effective against B. subtilis. Cadmium ferrocyanide has shown significant activity against M. luteus and P. fluorescence.